The DCF77 Decoder - Fast Code Generator - Skotnica, M. (Radioengineering Society, 1995)
Signal of the DCF amplitude-modulated transmitter, located in Braunschweig (Germany) is widely used for synchronizing of time information during different laboratory and field experiments. The full time information of this time normal is coded and presented within every minute using different length of second time marks. The knowledge of the exact time of occurrence of seismic events is the fundamental information during the seismic activity monitoring. With respect to the fact that the duration of individual records having sometimes a few seconds at minimum, the time generator ensuring the complete time information within every second, is needed. That is why the special timing device controlled by the DCF77 signal and generating every second the full time information was developed. Description of the function of decoder, internal clock and fast code generator implemented on the basis of FPGA circuits is the subject of this paper.
Keywords: DCF77 code decoder; synchronization; exact time measurement; fast code generator; FPGA circuit; shift register; paroty generator; timer